Vascular Malformation as an Orthopedic Problem (Review) - Huk, Yu.M.; Zyma, A.M.; Kincha-Polishchuk, T.A.; Cheverda, A.I.; Vyderko, R.V.; Skuratov, O.Yu. (TERRA ORTHOPAEDICA, 2020)
Summary. Scientific research is analyzed and highlights the modern views on the problem of orthopedic manifestations of vascular malformations. The achievements of scientists concerning etiology, pathogenesis, classification, orthopedic manifestations and treatment of pathology of the musculoskeletal system at vascular malformations are described. The authors also identified key unexplained practical issues of orthopedic manifestations in this nosology and announced ways to solve them.